Energy imbalance in oPOI ovarian granulosa cells is linked to reduced glucose bioavailability and metabolism - Weronika Marynowicz; Paulina Głód; Dawid Maduzia; Justyna Gogola-Mruk; Anna Ptak (Reproductive Biology and Endocrinology)
Abstract Background Premature ovarian insufficiency (POI), affecting approximately 1% of women under 40, is associated with impaired fertility. Occult POI (oPOI), an initiating form, is more challenging to detect but still allows potential success with IVF. Recent studies suggest a possible link between granulosa cell (GC) mitochondrial dysfunction and POI, as mitochondria are critical for energy production and reproductive function. Methods We recruited 81 women undergoing IVF which included: 25 women with oPOI defined as a low anti-Müllerian hormone (AMH) level (≤ 1.1 ng/mL) and under the age of 40 without raised follicle-stimulating hormone (FSH) levels and 56 healthy women (male or tubal factor infertility). Molecular analysis of GCs and CCs involved RT-qPCR and functional assays, including Seahorse metabolic profiling, fluorometric/luminescent enzyme activity tests, and mitochondrial fluorescent staining. Results We found that cumulus cells (CCs) from oPOI women showed reduced energy capacity. Similarly, GCs shifted toward glycolysis in oPOI, leading to lower ATP production. Despite similar glucose levels in FF between groups, oPOI CCs exhibited impaired glucose uptake and metabolism, with decreased GLUT1 and reduced hexokinase 2 (HK2) activity. In GCs, reduced GLUT1 but increased HK2 gene expression suggests compensatory metabolic reprogramming to maintain energy balance through enhanced glycolysis. Additionally, oPOI women had a lower level of estradiol, despite having a normal FSH level and a decreased estradiol/oocyte count. Conclusions This study indicated that in the case of oPOI, disruption may extend beyond the ovaries to impact the entire HPO axis. Furthermore, reduction of ATP production is connected with lower glucose uptake and may have implications for fertility in oPOI patients. It also highlights the potential for therapeutic strategies focused on improving glucose metabolism and mitochondrial biogenesis.